Development, education, and services in children with Down syndrome: a cohort analysis from a clinical database - Soccorso, Cara; Hojlo, Margaret; Pawlowski, Katherine; Lombardo, Angela; Davidson, Emily; Sargado, Sabrina; DePillis, Rafael; Baumer, Nicole (Frontiers in Psychology, 2024)
Background: Prior research has characterized neurodevelopmental phenotypes for Down syndrome (DS), but there is variability in age of milestone attainment and limited identification of early predictors of developmental trajectories. Additionally, less is known about receipt of education and services in relation to development.Objective: This study describes the delivery of education and therapies in the setting of general developmental and behavioral needs in a large clinical cohort of children with DS seen in a specialized Down Syndrome Program (DSP).The clinically collected data included 814 patients with DS who were seen at a specialty DSP at a large, tertiary pediatric care center from March 2018 to January 2023. Data were collected through caregiver-and clinician-reported history at clinical visits to the program.Descriptive frequencies were utilized to describe participant demographics, skills and behaviors, and receipt of services, across age groups in childhood.Results: Delays were present across all developmental domains; in particular delays in language, communication, and academic skills, and behavioral challenges were commonly reported. Almost all children received Early Intervention (EI) services, and many young children received non-public therapies after completing EI. Older participants demonstrated more impairments than younger age groups, yet received services at lower rates, particularly behavioral and speech language interventions.A snapshot of developmental skill attainment in individuals with DS is provided.Therapies to support the levels of need were reported at much lower frequencies than the level of need reported to target aspects of development and behavior. Several gaps in therapies and educational services were identified. There is an important need for tailoring supports, based on developmental level, to meet individual needs. These findings may help to inform policy change related to developmental and educational services for individuals with DS.